2010
DOI: 10.1007/s11064-010-0374-1
|View full text |Cite|
|
Sign up to set email alerts
|

Rostrocaudal Dynamics of CSF Biomarkers

Abstract: The rostrocaudal gradient (RCG) of markers present in cerebrospinal fluid (CSF) has not been studied adequately due to lack of appropriate control populations and ethical restrictions. The aim of this study is to understand the rostrocaudal gradient of CSF biomarkers. We contacted a study comparing CSF levels of seven biomarkers from cisternal (rostral) and lumbar (caudal) CSF obtained from patients with trigeminal neuralgia and tension-type headache. The RCGs of CSF/serum albumin ratio, 8-isoprostane. GFAP, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…Tarnaris et al compared Aβ 42 levels in cisternal and lumbar CSF and found a small rostrocaudal gradient. 45 In contrast, work by the Blennow group utilizing serial sampling measurements of 10 ml CSF did not demonstrate a spinal gradient for Aβ 42 . 46, 47 Based on these studies, if a gradient does exist from the site of reabsorption to the lumbar sampling site, the effect will likely be small and result in slight underestimation of the CSF clearance by our theoretical calculations.…”
Section: Discussionmentioning
confidence: 91%
“…Tarnaris et al compared Aβ 42 levels in cisternal and lumbar CSF and found a small rostrocaudal gradient. 45 In contrast, work by the Blennow group utilizing serial sampling measurements of 10 ml CSF did not demonstrate a spinal gradient for Aβ 42 . 46, 47 Based on these studies, if a gradient does exist from the site of reabsorption to the lumbar sampling site, the effect will likely be small and result in slight underestimation of the CSF clearance by our theoretical calculations.…”
Section: Discussionmentioning
confidence: 91%
“…Due to a limited access to simultaneously collected lumbar and ventricular CSF samples, no information is available about the rostrocaudal distribution of neuroproteins in the CSF. So far, ventricular and lumbar CSF samples from different populations have been used to characterize the protein distribution in the CSF [4,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of this data will need to be considered if the CSF was of ventricular or lumbar origin, as there is evidence of a rostrocaudal gradient with higher CSF GFAP levels in ventricular CSF (Tarnaris et al, 2010). Likewise, the presence of blood in the CSF was related to higher CSF GFAP levels in hydrocephalus (Naureen et al, 2013).…”
Section: Hydrocephalusmentioning
confidence: 97%